GE_GERICHTE P/4877/2024 vom 24. Februar 2025 - GE Cour de justice (2025)
VOL(DROIT PÉNAL);DOMMAGES À LA PROPRIÉTÉ(DROIT PÉNAL);VIOLATION DE DOMICILE;RUPTURE DE BAN;RETRAIT(VOIE DE DROIT) | CP.139; CP.144; CP.186; CP.291; CPP.386.al2